Strategi Komunikasi Pemasaran Makeup Artist Di Akun Instagram @Mymua1 Dalam Menjaga Kepercayaan Konsumen - Ananda, Firdha Cintia; Octaviani, Vethy; Sari , Sapta (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Marketing on social media platforms has become a key element in the marketing strategy for make up artists. In this context, the Instagram account @mymua1 is the center of attention as the main platform for interacting with consumers. This research was conducted with the aim of finding out how the marketing communication strategy for make up artists on the Instagram account @mymua1 maintains consumer trust.  The research method used was descriptive qualitative. This research uses data collection techniques through in-depth interviews, observation and documentation. The technique for collecting research information uses purposive sampling. The research results show that the marketing communication strategy implemented by @mymua1 has three theories, namely, segmentation, targeting and positioning. First, they maintain a positive impression by being friendly, not arrogant, and always listening to consumers' opinions or wishes. Second, @mymua1 maintains the quality of their services by continuing to learn and upgrade their skills. Third, @mymua1 maintains consumer trust by maintaining good communication, providing good suggestions for make up, and accepting suggestions from consumers. The conclusion of this research is that the marketing communication strategy for make up artists on the Instagram account @mymua1 in maintaining consumer trust has been running well and effectively, it can be seen that there are three marketing communication strategies being implemented by @mymua1.